Inkjet-printed organic electronics: Operational stability and reliability issues - Medeiros, M. C. R. (2015)
The operational stability of all-inkjet printed transistors is reported. At room temperature the threshold voltage shifts following a stretched exponential with a relaxation time τ=1×103 s. Two distinct trap sites active in different temperature ranges, one at 200-250 K and other above 310 K cause the electrical instability. Both types of traps capture holes and can be fast neutralized by photogenerated electrons. Optically induced detrapping currents confirm the differences in trap signature. It is proposed, that the traps have a common physical origin related to water. © The Electrochemical Society.